2018
DOI: 10.1038/s41467-018-03595-0
|View full text |Cite
|
Sign up to set email alerts
|

Publisher Correction: Anderson light localization in biological nanostructures of native silk

Abstract: The original PDF version of this Article contained errors in Equations 1 and 2. Both equations omitted all Γ terms. This has been corrected in the PDF version of the Article. The HTML version was correct from the time of publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Besides, based on Kirchhoff’s law of thermal radiation, strong absorption corresponds to high thermal emission. Therefore, the high thermal emittance of the cocoon is ascribed to the series of vibrational absorptions of silk protein structures (in Figure c). ,, The strong absorption is mainly due to the primary structure of fibroin proteina repetitive amino acid sequence, which can be roughly expressed as (Gly-Ser-Gly-Ala-Gly-Ala) n . , The repetitive amino acid sequence that has strong vibrational absorptions in the LWIR spectrum, such as N–H (3500–3100 and 1640–1550 cm –1 , amide I), CO (1680–1630 cm –1 , amide II), C–N (1300–1200 cm –1 , amide III), and C–H (3000–2850 and 1465–1375 cm –1 ), contributes to high thermal emittance for efficient radiative cooling of the silkworm cocoon. , …”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, based on Kirchhoff’s law of thermal radiation, strong absorption corresponds to high thermal emission. Therefore, the high thermal emittance of the cocoon is ascribed to the series of vibrational absorptions of silk protein structures (in Figure c). ,, The strong absorption is mainly due to the primary structure of fibroin proteina repetitive amino acid sequence, which can be roughly expressed as (Gly-Ser-Gly-Ala-Gly-Ala) n . , The repetitive amino acid sequence that has strong vibrational absorptions in the LWIR spectrum, such as N–H (3500–3100 and 1640–1550 cm –1 , amide I), CO (1680–1630 cm –1 , amide II), C–N (1300–1200 cm –1 , amide III), and C–H (3000–2850 and 1465–1375 cm –1 ), contributes to high thermal emittance for efficient radiative cooling of the silkworm cocoon. , …”
Section: Results and Discussionmentioning
confidence: 99%
“…To find out just how the natural creatures could spontaneously decrease the body temperature, researchers have carried out experiments to explore the mechanism of their thermal regulation instinct. Over the past few years, researchers reported that some natural creatures possess distinctive photonic structures for thermal regulation. On the one hand, their distinctive photonic structures usually give them the structural white or silver color for reflecting the sunlight and minimizing the heat gain. On the other hand, the structures are made of organic matter which has a high thermal emittance, and then, the microstructures could further enhance the thermal emittance for maximizing the heat loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation